Tantangan Hukum dalam Pertanahan: Studi Kasus Permasalahan Akta Tanah di Kantor Notaris Malang - Ari Tasyabani Muis; Defan Auli Rahmatillah (MLIJo: Journal of Law and Islamic Thought, 2026)
The rapid growth of information technology in Indonesia has given rise to a new legal framework known as cyber law, particularly governing electronic transactions (e-commerce). As internet usage expands, so does online commerce, but this growth also brings forth legal challenges, notably in consumer protection. This research employs a normative legal approach, combining statutory and conceptual analysis, supported by secondary data and empirical evidence. The findings indicate that resolving disputes in electronic transactions falls under civil law, as stipulated in the ITE Law and Consumer Protection Law. Disputes can be resolved through litigation (court proceedings) or non-litigation methods (such as arbitration, mediation, conciliation, and consumer dispute resolution bodies). However, litigation is often costly, time-consuming, and procedurally complex, prompting many to opt for non-litigation approaches that focus on negotiation and mutually beneficial solutions. Online Dispute Resolution (ODR) has emerged as a promising alternative, offering speed, cost-effectiveness, and cross-border capabilities. Despite its potential, ODR in Indonesia faces challenges due to insufficient technical regulations and infrastructure. To ensure effective, efficient, and equitable consumer protection in e-commerce, Indonesia needs stronger regulations, increased awareness, and better institutional support.